Childhood maltreatment and adult diseases in the general population: the mediating role of smoking and overweight in a time-sequence design - Klinger-König, Johanna; Streit, Fabian; Völker, Maja; Frank, Josef; Sekula, Peggy; Jaskulski, Stefanie; Leitzmann, Michael; Meinke-Franze, Claudia; Schmidt, Carsten O.; Keil, Thomas; Willich, Stefan N.; Pischon, Tobias; et al. (BMC public health, 2025)
Childhood maltreatment is associated with an unhealthier lifestyle in adulthood and an increased risk of mental and somatic health problems, although the underlying pathways remain unclear. This study examined whether smoking and overweight mediate the association between childhood abuse/neglect and frequent adult diseases, including cancer, myocardial infarction, stroke, type 2 diabetes, chronic obstructive pulmonary disease, depression, and anxiety.
Gesehen am 10.12.2025